2017
DOI: 10.7324/japs.2017.70827
|View full text |Cite
|
Sign up to set email alerts
|

A Cross Sectional Survey on the Knowledge and Attitude towards the Use of Multivitamin Products among the Students of a Medical University in the U.A.E

Abstract: Background and Objective:The consumption of multivitamin products for their benefits towards maintenance of health has often been debated upon. This study attempts to assess the knowledge and attitude of the students of a medical university towards the use of multivitamin products. Materials and Methods: A descriptive cross-sectional questionnaire based study was conducted on 319 student participants of a medical university in the U.A.E. Data was analyzed using SPSS version 22 and Pearson Chi Square Test. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
3
1
0
Order By: Relevance
“…The results indicated that females, older adults (>40 years), and expatriates of Asian and Arabic ethnicities were more likely to report using DDS to prevent or treat COVID-19. The positive association between older age and the use of DDS aligns with findings in the literature from the UAE ( Rosalia et al, 2017 ) and elsewhere ( Bogale et al, 2018 , Kofoed et al, 2015 ). Previous studies have similarly noted sex disparities in DDS use in the UAE ( Alomar et al, 2019 ), and elsewhere ( Alqrache et al, 2021 , Kofoed et al, 2015 , Pouchieu et al, 2013 ), whereby women were shown to use DDS more than men, though some other studies reported contradictory findings ( Abdullah Alotiby and Naif Al-Harbi, 2021 , Radwan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results indicated that females, older adults (>40 years), and expatriates of Asian and Arabic ethnicities were more likely to report using DDS to prevent or treat COVID-19. The positive association between older age and the use of DDS aligns with findings in the literature from the UAE ( Rosalia et al, 2017 ) and elsewhere ( Bogale et al, 2018 , Kofoed et al, 2015 ). Previous studies have similarly noted sex disparities in DDS use in the UAE ( Alomar et al, 2019 ), and elsewhere ( Alqrache et al, 2021 , Kofoed et al, 2015 , Pouchieu et al, 2013 ), whereby women were shown to use DDS more than men, though some other studies reported contradictory findings ( Abdullah Alotiby and Naif Al-Harbi, 2021 , Radwan et al, 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…The increased intake of DDS in this study was also associated with the type of living residence suggesting an association between DDS use and lower socioeconomic status. The evidence from the literature on the relationship between the use of DDS and socioeconomic status is inconclusive ( Rosalia et al, 2017 ). However, previous studies from the UAE and from other high-income countries associated the use of alternative remedies including DDS with higher income ( Alomar et al, 2019 , Clarke et al, 2015 , Frass et al, 2012 , Kim et al, 2013 , Reid et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding age, the older population used DS most frequently, possibly due to the vulnerability of their immune system and the possibility of chronic diseases, which is consistent with the results of other studies in the UAE (Rosalia et al. , 2017; Radwan et al.…”
Section: Discussionsupporting
confidence: 89%
“…Answering the second research question, in particular, this study has shown that certain demographic variables such as age, nationality, comorbidities, smoking and employment status influence consumption and individual attitudes toward DS consumption. Regarding age, the older population used DS most frequently, possibly due to the vulnerability of their immune system and the possibility of chronic diseases, which is consistent with the results of other studies in the UAE (Rosalia et al, 2017;Radwan et al, 2022) and in the Danish population (Kofoed et al, 2015). DS In terms of nationality, nationals of countries outside the UAE accounted for the highest percentage of users of DS, which is to some extent consistent with the findings of Radwan et al (2022), who reported that the majority of users of DS were Asian, possibly due to the widespread use of DS in several Asian cultures and traditions and the social and cultural acceptance of its use as a highly effective treatment modality (Shim and Kim, 2018).…”
Section: Dietary Supplements Insupporting
confidence: 90%